A influ??ncia da pr??tica da atividade f??sica e da socializa????o na qualidade de vida do idoso: um estudo nos pontos de encontro comunit??rio do Distrito Federal - Azevedo Filho, Elias Rocha de (2016)
People's lives have been prolonged due to a new behavior, where there is a concern with the improvement in the quality of life and the strengthening of health promotion actions. Physical and mental health received important contributions from physical activity and socialization, benefiting all age groups, especially those living in old age. The Third Age Academy (TAA) is a program already inserted in several states of Brazil, often located in Community Meeting Points (CMP) and having equipment designed for physical activity. The objective of this study was to evaluate the extent to which the practice of physical activity in the Community Meeting Points of the Distrito Federal provides changes in mood, socialization and quality of life of the elderly from 60 years old. This quantitative, transversal and descriptive study was carried out with 119 elderly people with sociodemographic, mood measures and referring to physical activities, socialization process and quality of life. From this research, it was concluded that the PEC increase the quality of life and the socialization, as well as reduce the indices of anxiety and depression of the same ones.